2022
DOI: 10.3390/ijms23115896
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Bacteria and the Immune System for Cancer Immunotherapy: The α-GalCer Alliance

Abstract: Non-conventional T cells, such as γδ T and invariant natural killer T (iNKT) cells, are emerging players in fighting cancer. Alpha-galactosylceramide (α-GalCer) is used as an exogenous ligand to activate iNKT cells. Human cells don’t have a direct pathway producing α-GalCer, which, however, can be produced by bacteria. We searched the literature for bacteria strains that are able to produce α-GalCer and used available sequencing data to analyze their presence in human tumor tissues and their association with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Prevotella7 is a specific strain or subgenus of gut microorganisms belonging to the Prevotella genus, and it has previously been recognized for its roles in dietary and intestinal health [ 46 ]. In 2022, Arsenij U et al found Prevotella in mouse glioblastoma tissue and found that Prevotella can produce Alpha-galactosylceramide (α-GalCer), a metabolite that stimulates invariant natural killer T (iNKT) cells to exert anticancer effects [ 47 ]. This finding is consistent with our findings suggesting that increasing the abundance of Prevonella may play a role in immunotherapy for glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella7 is a specific strain or subgenus of gut microorganisms belonging to the Prevotella genus, and it has previously been recognized for its roles in dietary and intestinal health [ 46 ]. In 2022, Arsenij U et al found Prevotella in mouse glioblastoma tissue and found that Prevotella can produce Alpha-galactosylceramide (α-GalCer), a metabolite that stimulates invariant natural killer T (iNKT) cells to exert anticancer effects [ 47 ]. This finding is consistent with our findings suggesting that increasing the abundance of Prevonella may play a role in immunotherapy for glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Atractylenolide I, a component extracted from Rhizoma Atractylodis macrocephalae, may inhibit dysbacteriosis by regulating TLR4/MyD88/NF-κB signaling 193 . Alpha-galactosylceramide, produced by bacteria such as Bacteroides fragilis, Bacteroides vulgatus, and Prevotella copri, exerts antitumor effects by activating nonconventional T cells, such as invariant natural killer T (iNKT) cells and γδ T cells 194 . AGPs exert chemopreventive effects by restoring dysbiosis and maintaining enteric homeostasis 195 .…”
Section: Treatments Targeting Kras and The Tmementioning
confidence: 99%
“…(10/27) were elevated in CF versus controls. The majority of SCFA producing bacteria have been linked to anti-inflammatory and antitumourigenic responses in the colon [27][28][29][30][31][32][33][34][35][36] (Figure 3). SCFA producing bacteria with tumourigenic responses such as Flavonifractor, Dialister, Acidominococcus, B. fragilis, R. gnavus, R. torques were all elevated in CF [28,37,38] (Figure 3).…”
Section: Genus and Species Level Taxonomic Diversitymentioning
confidence: 99%